2022
DOI: 10.1155/2022/5497991
|View full text |Cite
|
Sign up to set email alerts
|

Licoflavone A Suppresses Gastric Cancer Growth and Metastasis by Blocking the VEGFR-2 Signaling Pathway

Abstract: Objectives. Licoflavone A (LA) is a natural flavonoid compound derived from the root of Glycyrrhiza. This study investigated the antitumor effect and underlying molecular mechanisms of LA against gastric cancer (GC) in vitro and in vivo. Materials and Methods. A CCK8 assay was used to measure the antiproliferative activity of LA in human GC SGC-7901, MKN-45, MGC-803 cells, and human GES-1 cells. Target prediction and protein-protein interaction (PPI) analysis were used to identify the potential molecular targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Licoflavone A ( Figure 2 , 12) affected the proliferation, cycling, apoptosis, migration, invasion, and EMT of VEGF-stimulated MKN-45 cells by targeting VEGFR-2 and inhibiting the PI3K/AKT and MEK/ERK signaling pathways. 87 Furthermore, in AGS cells, epigallocatechin-3-gallate (EGCG) ( Figure 2 , 14) suppressed IL-3-induced VEGF production and angiogenesis by reducing STAT6 activity, presenting a novel approach for anti-tumor angiogenesis. 69 Although studies have consistently identified the involvement of VEGF in tumor angiogenesis, further investigations are needed to elucidate the precise pathways and mechanisms ( Figure 4 ).…”
Section: Flavonoids For Fighting Against Gcmentioning
confidence: 99%
“…Licoflavone A ( Figure 2 , 12) affected the proliferation, cycling, apoptosis, migration, invasion, and EMT of VEGF-stimulated MKN-45 cells by targeting VEGFR-2 and inhibiting the PI3K/AKT and MEK/ERK signaling pathways. 87 Furthermore, in AGS cells, epigallocatechin-3-gallate (EGCG) ( Figure 2 , 14) suppressed IL-3-induced VEGF production and angiogenesis by reducing STAT6 activity, presenting a novel approach for anti-tumor angiogenesis. 69 Although studies have consistently identified the involvement of VEGF in tumor angiogenesis, further investigations are needed to elucidate the precise pathways and mechanisms ( Figure 4 ).…”
Section: Flavonoids For Fighting Against Gcmentioning
confidence: 99%